Risk Factors for Stunting under Two-Year-Old Children in Surabaya - Maulina, Cintia; Rachmayanti, Riris Diana (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: Indonesia is the fifth-highest number of stunting incidence in the world. Mothers’ conditions before, during, and after pregnancy were as major cause of stunting. This study aims to analyze the risk factors of stunting among children under two in Surabaya. Method: Analytical survey with a cross-sectional design was conducted on 233 selected samples from December 2019 to January 2020. Dataset for the Chi-square test comes from the measurement of the body height of under two-year-old children and interviews with mothers.Results: It shows that factor related to stunting under two-year-old children in Surabaya is history of Antenatal Care (ANC) during pregnancy (p-value =0,005). Pregnant mother who did non-routine ANC may risk 0,360 times higher to stunting condition. The incidence of stunting in Surabaya is not influenced by factors such as age, education, work status, income, history of Fe and protein consumption. Health office shoud encourage pregnant women to do ANC more than 4 times during pregnancy.